Influence of Auditing Firms Intellectual Capital Development on Requirements Availability for Big Data Analysis : Field Study on Auditing Firms in Gaza Strip (Journal of Accounting and Financial Studies ( JAFS ), 2023)
This study aimed to highlight the conceptual framework of intellectual capital, by defining its concept, characteristics, importance, and the importance of its development in auditing institutions. The study dealt with development of intellectual capital through the development of its three components: human capital, structural capital, and relationship capital. The study also aimed to clarify the conceptual framework of big data, its importance, characteristics, and analysis requirements. Three requirements have been identified that need to be met for the analysis of big data in auditing firms: technological requirements, human requirements, and organizational requirements.  In order to achieve the objectives of the study and test its hypotheses, the analytical descriptive approach was used. A field study was conducted using a survey list distributed to the auditing facilities operating in the southern governorates of Palestine (Gaza Strip). The field study results concluded that there was a positive influence for the development of intellectual capital with its three components: human capital, structural capital, and relationship capital) and the requirements for big data analysis are available in auditing firms operating in the southern governorates.